Performance of non woven synthetic fabric and disc filters for fertirrigation water treatment (Scientia Agricola, 2004)
Obstruction of emitters caused by the presence of solid particles in the water raises the cost and maintenance of trickle irrigation systems, and might compromise their utilization. This research was performed through test fields, with the objective of evaluating the performance of a disc filter (130 microns) and a non woven synthetic fabric filter on the removal of physical, chemical and biological impurities from the irrigation water, which may cause emitter obstruction during fertirrigation processes. The evaluation criteria of the impurities present in the irrigation water, were based on studies performed on trickle irrigation systems. Specifically, physical, chemical and biological parameters analyzed in the inflow and outflow water from both filters were: pH, turbidity, total suspended solids, salinity, total iron, sulphites, manganese, algae and bacteria. Results pointed to chemical factors, which presented medium clogging risks to the emitters; those factors were: pH, total iron and sulphite concentration. All the other parameters of water quality did not present clogging risks. A comparative analysis of head loss evolution, according to the filtered volume, was also atempted Non woven synthetic fabric filter presented a higher evolution when compared to the disc filter.